PTSD Among Substance Abusers: Prevalence of Various Trauma Types and the Concurrence of Addiction and Mental Disorders on PTSD - Ísabella Guðmundsdóttir 1994- (2018)
Previous studies have reported that individuals suffering from substance abuse are more likely to be exposed to traumatic events and are at higher risk for developing PTSD. The objective of the study was to examine if there was a difference between the types of trauma substance abusers experience compared to a control group, PTSD rates were also examined and main associations of substance abuse and depression with PTSD were assessed. Additionally, interaction effects were examined. Participants in this study were substance abusers on a waiting list to seek treatment for at Teigur (N=51). Participants in the control group were students from Reykjavík University (N=111). The DASS-21 questionnaire was used to assess depression, anxiety and stress among participants, the LEC-5 questionnaire was presented to examine different trauma types and PCL-5 questionnaire measured PTSD symptoms. Substance abusers reported a significantly higher prevalence of trauma types, namely; sexual abuse, physical assault, assault with a weapon and severe human suffering than the control group. In the substance abusers group, 75% met the criteria for PTSD in compared to 15 % in the control group. The prevalence of depression and anxiety was significantly higher among substance abusers. Additionally, Factorial ANOVA showed a main association between substance abuse and PTSD as well as between depression and PTSD. Interaction effects were not significant. Results indicate that substance abusers experience more violent trauma than the control group and PTSD is prevalent among these individuals. Therefore, it is important to provide them with the support that takes these facts into account. Keywords: Trauma, PTSD, substance abuse, depression Rannsóknir hafa sýnt fram á að einstaklingar sem glíma við fíkniefnavanda eru líklegri til að lenda í áföllum og eru í meiri áhættu á að þróa með sér áfallastreituröskun. Markmið rannsóknarinnar var að skoða muninn á því hvernig tegundir áfalla fíklar lenda í miðað við samanburðarhóp. Algengi ...